Determination of periplocymarin in human blood and urine by high-performance liquid chromatography-mass spectrometry - Chen Jian Xia; Wei Qing Tao; Chen Fan; Wu Hao; Fu Ying Qing; Wu Zhi Gui; Dai Xin Hua; Ye Yi; Yan You Yi; Liao Lin Chuan (Wolters Kluwer Medknow Publications, 2017)
A simple, rapid and sensitive liquid chromatography with tandem mass spectrometry method for the determination of periplocymarin in human blood and urine was developed. The digoxin-d3 was used as an internal standard. Periplocymarin and digoxin-d3 (IS) were processed with ethyl acetate by liquid-liquid extraction. The chromatographic separation was performed on a Shim-pack XR-ODSIII C18 column with a 7 min gradient elution using methanol-ammonium formate (5 mmol/L) as mobile phase at a flow rate of 0.3 mL/min (65:35, v/v). The detection was performed on a triple quadrupole tandem mass spectrometer using positive-ion mode electrospray ionization in selected reaction monitoring mode. The periplocymarin was well separated from the internal standard. Two calibration curves were linear within the concentration range 0.01-1 μg/mL. The limit of detection and quantification of blood and urine samples were both estimated at 0.005 and 0.01 μg/mL. The interday and intraday precisions, accuracy, and recovery were assessed to verify this method. The results showed that the method was suitable for the determination of periplocymarin in forensic toxicological analysis and clinical diagnosis.